The urban choices the city and its critics - Starr, Roger (Pelican book, 1967)
Urban Choices deals with the ultimate questions of city life in the United States; it attempts to establish a set of values by which the decisions of urban governments can be judged. It presents a clear assessment of the nation's urban ills and makes specific and sound suggestions form their cure.